An overview of the development of composites containing Mg and Zn for drug delivery - Niazvand, Firooze; Cheshmi, Amir; Zand, Maryam; NasrAzadani, Reyhaneh; Kumari, Beena; Raza, Ali; Nasibi, Shima (Journal of Composites and Compounds, 2020)
Drug delivery is known as the administration of drugs using suitable vehicle for achieving effective treatment with no unwanted effects. In recent years, various composite materials have been developed and evaluated for being used in different biomedical fields such as wound dressings, cardiac prosthesis, tissue engineering, and drug delivery. Zinc is the second most available element after Fe in our body. Nanoparticles based on metal oxides, such as zinc oxides and Zn-containing composites, can be considered as viable platforms for some biomedical uses, especially for drug delivery applications. Mg composite biomaterials are also suggested for diverse biomedical applications due to their good mechanical properties, biocompatibility, and bioactivity. This paper highlights applications of zinc and magnesium-based composites in development of drug delivery systems.